EXPERTISE, TRUST, COMMITMENT AND BEHAVIOR INTENTIONS IN RELATIONSHIP MARKETING: CASE STUDY NORTH BANDUNG DAIRY COOPERATIVE - HARSINI SOETOMO (Jurnal Bisnis dan Akuntansi, 2002)
Most of farmers in Indonesia are small scale, so the role of an agribusiness co-operative is very important in helping them to develop their business. The dairy co-operative is one of such type of agribusiness co-operative. The working partnership between co-operative and its members can ve categorized as relational, a working partnership in channel of distribution. This study exhibited co-operative's expertise in managing the working partnership impacts on trust, which in turns affects commitment relationship and loyalty of the members.